Nilai Responsif Gender dalam Pembelajaran Bahasa Arab - Maslihah, Rizka Eliyana (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
Abstract The issue of gender responsiveness become a subject of study that is widely discussed. Discourse about the equality of men and women reap many pros and cons from various circles, as the result of social construction differences that affect the perspective of mindset. This article intends to describe the gender-responsive value contained in the material of Arabic language learning. Where the material presented includes the use of mudzakar and muannats vocabulary, where both have equal status without any stereotypes and subordinates of them. This article was written using library research; the author analyzed the use of mudzakar and muannats vocabulary in a balanced manner, as well as the use of various gender discriminations in the form of gender stereotypes and gender-based violence found in Arabic textbooks in grades IV and VI of Islamic Elementary School (MI). Based on the analysis result, the researcher concludes that gender-responsive emphasis has been appearing in Arabic language teaching materials, but it needs more. So, in the next, gender discrimination will not be found in the Arabic language teaching material of Islamic Elementary School (MI). Keywords: Value, gender responsiveness, learning material, gender discrimination.   ملخص أصبحت الإشاعة عن استجابة الجنس بحثا مرحوبا فى مجال المعارف. وحصد البحوث فى تكافؤ الرجال والنساء الموافقة والمعارضة من قبل الاجتماعية. حيث أن الاختلاف فى بنية الاجتماعية سيؤدي إلى الاختلاف فى ضوء العقليات. وكتبت هذه المقالة للكشف عن التصور الشامل للنتائج  من استجابة الجنس فى مادة تعليم اللغة العربية. حيث اشتملت المادة فى استخدام المفردات المذكّر والمؤنث. بالإضافة إلى ذلك، وجد تكافؤ الدرجة دون النمطية وثانوية النساء فى المجتمع. وكتبت هذه المقالة بمدخل البحث المكتبي للتحليل عن استخدام المفردات المذكّر والمؤنث بالتكافؤ، دون النمطية وثانوية النساء فى الكتب المدرسي للفصل الرابع إلى السادس لمستوى المدرسة الإبتدائية. وحصلت الكاتبة على النتيجة كما يلي: ظهرت التركيز من النتائج لاستجابة الجنس فى مادة تعليم اللغة العربية جيّدة، ولكن يحتاج التركيز إلى التقوية، للوصول إلى عدم تمييز الجنس فى مادة اللغة العربية لـهذا المستوى. الكلمات الرئيسية: النتيجة، استجابة الجنس، مادة التعليم، تمييز الجنس   Daftar Pustaka Abu Sholeh, Badruddin. Al-Madkhal Ila Al-Lughah Al-‘Arabiyah. Beirut-Lebanon: Daar al-Syarif al-Araby, t.t. Ali, Atabik, dan Zuhdi Muhdlor. Kamus Kontemporer Arab Indonesia. Yogyakarta: Multi Karya Grafika, 1998. Asrohah, Hanun, dan Anas Amin Alamsyah. Pengembangan Kurikulum. Surabaya: Kopertais Wilayah IV, 2010. Bahruddin, Uril. Tatwir Manhaj Ta’lim Lughah Al-Arabiyah wa tathbiqihi ’ala maharah al-kitabah. Malang: UIN Maliki Press, 2010. Cholil, Mufidah. Isu-Isu Gender Kontemporer dalam Hukum Keluarga. Malang: UIN Maliki Press, 2010. Gholayani, Musthofa. Jami’ud Durus Al-‘Arobiyah. Mesir: Daarul Hadits, 2005. Mistiani, Wiwin. “Keadilan Gender dalam Penilaian Hasil Belajar.” Musawa: Jurnal Studi Gender dan Islam UIN Sunan Kalijaga Yogyakarta Vol. 7 No. 2 : Desember 2015. Muhammadun, Muzdalifah. “Penanda Gender dalam Perspektif Bahasa Arab dan Bahasa Indonesia.” Al-Maiyyah (Jurnal P3M IAIN Parepare) Vol. 9 No. (Juni 2016). Rukabi, Jawdat al-. Thuruq Tadris al-Lughah al-’Arabiyyah. Damaskus: Dar al-Fikr, 1996. Sanjaya, Wina. Kurikulum Pembelajaran. Jakarta: Prenada Media Group, 2008. Shodiq, Muhammad Jafar. “Perspektif Kesetaraan Gender dalam Buku Bahasa Arab Siswa MTs Pendekatan Saintifik 2013.” Fenomena (Jurnal Penelitian IAIN Samarinda) Vol. 8 No. 1 (2016). Solichin, Mohammad  Muclis. “‘Pendidikan Agama Islam Berbasis Kesetaraan Gender.’” Tadris-Jurnal Keguruan dan Ilmu Tarbiyah STAIN Pamekasan Vol. 1 No. 1 (2016). Thu’aimah, Rusydi Ahmad. Manahij Tadris al-Lughah al-’Arabiyyah bi al-Ta’lim al-Asasi. Kairo: Dar al-Fikr al-’Arabi, t.t. Umar, Nasaruddin. Argumen Kesetaraan Gender. Jakarta: Paramadina, 2001. Wekke, Ismail Suardi. “Gender dalam Materi Belajar Bahasa Arab di Pesantren.” Turats: Jurnal Penelitian & Pengabdian LPPM IAIN Imam Bonjol Padang Vol. 1 No. 1. (Juni 2013). Yunus, Mahmud. Al-Tarbiyah wa Al-Ta’lim “Juz 1c.” Ponorogo: Gontor Press, t.t.